ANTARA FLAT DAN SLEDING - Dion Yanuarmawan (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2017)
Small and Medium Enterprises (SME) products are home industry based on specific future of the culture, for example “Batik” is culture of Yogyakarta society, “Tahu Poo” is a specific of Kediri, “Tempe Sanan” is a specific future of Malang beside its apel, “Brem” is a specific future of Madiun, and other examples which can not be mentioned one by one. Capitalization is a big problem for SMEs, because when they needed loans in having an affor to develop their business, they felt difficult to get it. The existence of banks for SMEs were really hoped because bank had a role as financial intermediary between surplus unit and deficit unti. Beside, it was as an institution which could give a facility of payment. Loans which were given by the bank to the society. Inthis case, we called it “SMEs”. SMEs used several systems in payment, there are: Flat Interest System and Sliding Interest System. This research used quantitative method. The researchers used descriptive quantitative because the researchers intended to understand and analyze the comparison of flat interest system and sliding interest system. The data of this research used primary and secondary data. Primary data of this research was obtained through interviews the parties who were related tho the statements of the problems. The primary data source of this research were the SMEs owner (subject) who got loans from the bank and charged with Flat Interest System and Sliding Interest System. Secondary data of this research were SMEs’s Financial Statement